Walking in Ahmedabad - Ramos, M. (Paydayatricks - Pedestrians in Ahmedabad, 2015)
Walking is not only a primordial human tool for motion. It is an essential cognitive and socializing tool. It is also a formidable means to personal health and well-being. The progressive motorization of societies has led to a dramatic imbalance between people's needs for walking and the spatial, organizational and statutory demands of gas-powered vehicles. It has resulted in a multitude of public health issues (either traumas caused from direct impact or pollution-related diseases), and in the ghettoization of pedestrians in the public space of urban areas. Most public health and mobility specialists agree today that the unrestricted use of privately owned and used motor vehicles in cities is a major social and economic strain that can only be tackled through a systematic, sustained and inclusive policies of promotion of softer modes of transportation, and the rebalancing of the needs of mobility with those of accessibility. Such policies are better pursued when rested upon the convergent tools of structural redesign of public spaces, of education, of enforcement, and of better legal protection of fragile road users. But to be truly effective, this paradigm shift requires public awareness and the mobilization of decision-makers, law-enforcers, experts in social sciences and technology, and interested stake-holders from the civil society. This Seminar proposes to do just that: create a forum for discussion and intervention that reflects on the problems and needs of pedestrians in Ahmedabad as a means to bring in a more sustainable vision for the mobility of the city.